The application of supercritical CO2 based technology for curcumin particle processing - Kurniawansyah, F.; Mammucari, R.; Foster, Neil (2016)
© 2016 Trans Tech Publications, Switzerland. Supercritical CO 2 is commonly used in the processing of natural products due to several advantageous factors such as inexpensiveness, moderate operating parameters and simple purification step. In the processing of phyto-pharmaceuticals, CO 2 has been used mostly for extraction, purification and particle formation. This article is a review of supercritical particle formation processes applied to phenolic compounds, specifically curcumin. In summary, supercritical technologies constitute a process platform for the modification of curcumin physicochemical properties. The use of supercritical CO 2 as a solute, solvent or anti-solvent in curcumin processing enabled the production of material with particle size as small as 15 nm and improved antioxidant activity.